National leadership for legislating longer product lifetimes: French policies and their interaction with European Union policies - Dalhammar, Carl; Vonderscher, Flavie; Leonet, Sandar; Richter, Jessika Luth (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Currently, the European Union (EU) is the “green leader”, globally, in adopting policies to support longer product lifetimes. One reason for this state of affairs is that EU Member States are adopting progressive policies, which put pressure on the EU to set EU-wide laws to replace national ones. The main reason for this situation is that national rules may lead to distortions in trade in the EU Single Market, as corporations will find it difficult to be able to comply with different national rules and would prefer EU-wide standards. Currently, France is the undisputed leader in adopting policies for longer lifetimes, through policies including criminalization of planned obsolescence, modulated fees, repair policies, banning destruction of unsold products, and national indexes for repairability and durability of products. When the EU adopts similar policies, this can have several positive implications, but there can also be negative effects, for instance that the EU rules are less progressive than the national ones. The aim of this paper is to discuss the key benefits and drawbacks with EU harmonization of national rules, using France as an example. This paper maps the key French policies supporting longer product lifetimes and the upcoming EU rules aiming for EU-wide harmonization. Finally, we describe one policy where EU rules are likely to be less progressive than the French ones, mandatory repair information to consumers, to exemplify key trade-offs with harmonization.